Combined Effect of Bel and Curry Leaves Supplementation on the Performance of Anestrous Cattle - Priyadarshinee, P.; Sethy, Kamdev; Swain, R.K.; Mishra, S.K.; Behera, K.; Pradhan, S.K.; Tripathy, S. (Indian Journal of Animal Nutrition, 2022)
To assess the effect of bel and curry leaves supplementation on the performances of anestrous cattle, 40 cross bred cattle (24 heifers and 16 cows) were divided into four groups of 10 animals each (containing 06 heifers and 04 cows) following complete randomised design. Group T1: control (concentrate mixture and paddy straw), group T2: group T1 + dried bel leaves @ 50g/animal/day, group T3: group T1+ dried curry leaves @ 50g/animal/day, andÂ  group T4: group T1 + dried bel leaves @ 50g/animal/day and Dried curry leaves @ 50g/animal/day. The experiment was performed for 60 days. The growth performances were measured in terms of body weight and average daily gain (ADG). Blood collection was done at the end of the experiment for assessment of blood biochemical and antioxidant status of the animals. Results revealed significant improvement in antioxidant enzyme status and reproductive performances and decreased in total cholesterol and triglycerides concentration in treatment group as compared to control group. Higher percentage of conception was achieved in group T4 (50%) followed by group T3 (30%) and group T2 (20%). The least percentage was in group I (0%). Therefore, it was concluded that supplementation of bel and curry leaves prevent stress and improved the reproductive status of anestrous cattle.